Loss of Hepatic CEACAM1: A Unifying Mechanism Linking Insulin Resistance to Obesity and Non-Alcoholic Fatty Liver Disease - Heinrich, Garrett; Ghadieh, Hilda E.; Ghanem, Simona S.; Muturi, Harrison T.; Rezaei, Khadijeh; Al-Share, Qusai Y.; Bowman, Thomas A.; Zhang, Deqiang; Garofalo, Robert S.; Yin, Lei; Najjar, Sonia M. (Frontiers in Endocrinology, 2017)
The pathogenesis of human non-alcoholic fatty liver disease (NAFLD) remains unclear, in particular in the context of its relationship to insulin resistance and visceral obesity. Work on the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) in mice has resolved some of the related questions. CEACAM1 promotes insulin clearance by enhancing the rate of uptake of the insulin-receptor complex. It also mediates a negative acute effect of insulin on fatty acid synthase activity. This positions CEACAM1 to coordinate the regulation of insulin and lipid metabolism. Fed a regular chow diet, global null mutation of Ceacam1 manifest hyperinsulinemia, insulin resistance, obesity, and steatohepatitis. They also develop spontaneous chicken-wire fibrosis, characteristic of non-alcoholic steatohepatitis. Reduction of hepatic CEACAM1 expression plays a significant role in the pathogenesis of diet-induced metabolic abnormalities, as bolstered by the protective effect of hepatic CEACAM1 gain-of-function against the metabolic response to dietary fat. Together, this emphasizes that loss of hepatic CEACAM1 links NAFLD to insulin resistance and obesity.